Scapular dyskinesis-based exercise therapy versus multimodal physical therapy for subacromial impingement syndrome in young overhead athletes with scapular dyskinesis: a randomized controlled trial - Wen, M.; Hu, X.; Bao, G. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Objective To compare the efficacy and underlying mechanisms of scapular dyskinesis-based exercise therapy (SDBET) and multimodal physical therapy (MPT) in young male overhead athletes with subacromial impingement syndrome (SIS) and scapular dyskinesis (SD).